Geneza i charakter prawny stopni naukowych: [Genesis and legal character of scientific degrees] (Studia Prawnicze / The Legal Studies, 1982)
Scientific degrees, as indicators of the development of science, play such im- portant role in organizational systems of science that structural changes within the latter occur almost simultaneously with changes of legal regulation.It was the author’s intention to bring closer some of the issues concerning ge- nesis and character of scientific degrees, as an illustration of present system of degrees in Poland.Beginning with etymology of institutions and titles from the period of organ- ization of the first European universities, the author brings the reader’s attention to their “guild” — like character and to two opposed tendencies: that of the autonomy of the universities and the superiority of authorities, both accompanying the growing need for staff with scientific degrees. Also, those elements of historical organization of the universities in Poland were presented (including the influence of partitions of Poland), which led to the birth of first Polish law on academic schools.In further parts of the study, chosen issues concerning scientific degrees of several European states were discussed: autonomous French model, Soviet model based on the principle of domination of administration, German model based onthe principle of division of management, and highly traditional British model. As a separate illustration, some socialist solutions based on common model were presented.Although the above issues are marginal from the point of view of proper scientific research, they always influence legal and organizational solutions, and therefore to some extent constitute an introduction to research in the domain of positive law.